Свободу змею Горынычу! - Благов Владимир Иванович (Новые сказочные повести, 2011)
Экземпляры: М/а ДБ (20131110) / Инвентарный номер: 100264 / Цена: 73.20 / Авт.знак: Б 68 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6